2017
DOI: 10.3390/su9060996
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Aging Effect on Properties of Sustainable Pavement Asphalts Modified by Waste Rubber and Diatomite

Abstract: Waste utilization has gained more and more interest. In this study, crumb rubber and diatomite were used to modify asphalt binder and the short-term aging effects on the properties of modified asphalts were evaluated. Three kinds of modified asphalt were prepared; they are diatomite modified asphalt (DA), crumb rubber modified asphalt (RA), and diatomite and crumb rubber compound modified asphalt (DRA). Thin film oven test (TFOT) was used to simulate short-term aging in the laboratory. Penetration, softening p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Relevance is essentially the difference in geometry between curves. The closer the geometry is, the closer the development trend is, and the greater the degree of relevance is [ 37 , 38 ].…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…Relevance is essentially the difference in geometry between curves. The closer the geometry is, the closer the development trend is, and the greater the degree of relevance is [ 37 , 38 ].…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…Dynamic viscosity is a basic rheological property which represents the resistance to shearing deformation and affects the asphalt pavement construction (Liu et al, 2018;Liu et al, 2017). Viscosity is an important a NOTE: A35P is an industrial as-sold bitumen; therefore, it already includes crosslinking/stabilising agents (i.e., sulphur) that promote better compatibility between the bitumen and polymer phase.…”
Section: Conventional Bitumen Testsmentioning
confidence: 99%
“…Therefore, there have been some studies focusing on diatomite composite modified to improve the comprehensive performance of the diatomite modified asphalt binder. For example, Liu et al [ 18 , 19 ] found that the softening point, viscosity and needle penetration index of the diatomite composite rubber powder (RP) modified asphalt increased with the increase of diatomite content, while needle penetration and ductility decreased. Liang et al [ 20 ] found that with the addition of RP and diatomite increased, the ability of instantaneous elastic deformation, viscoelastic deformation, irreversible permanent deformation, and the relaxation modulus of the diatomite/RP composite modified asphalt mixtures can be improved.…”
Section: Introductionmentioning
confidence: 99%